ACMT Position Statement: Preventing Cannabis Exposures in Children (2026) - Robert G. Hendrickson; Maryann Mazer-Amirshahi; Caitlin Bonney; Michele Burns; Diane P. Calello; Suzanne Doyon; Jeremy Hardin; Hannah Hays; Diane E. Hindman; Erica Liebelt; Michael J. Moss; Lewis Nelson; et al. (Journal of Medical Toxicology, 2026)

Beyond dive shape: the identification of fine-scale vertical movements reveal within-dive behavioural structure in a pursuit-diving seabird - Astrid Dedieu; Mark Jessopp; Sam L. Cox (Marine Biology, 2026)
Understanding how diving predators exploit prey in dynamic marine environments provides insight into their foraging strategies, energetic trade-offs, and capacity to adapt to changing conditions. While traditional classifications of dive shape have provided valuable albeit coarse insights, fine-scale behaviours embedded within dives, such as prey encounter/capture attempts, can be overlooked. We used time-depth recorders (TDR) deployed on Atlantic puffins ( Fratercula arctica ) between 2021 and 2025 on Skellig Michael, County Kerry, Ireland (51.7707°N, 10.5405°W) to detect fine-scale vertical undulations (“wiggles”) in dives as proxies for prey-capture attempts. We used a broken-stick model to divide dives into segments and built a custom function to identify wiggles within segments. Wiggle occurrence differed significantly among dive phases ( p < 0.001). Wiggles were most frequent during the ascent and bottom phases. Less than 10% of wiggles occurred during descent phases, despite descent making up 30.3% of the time spent diving. Our findings indicate that puffins, like other pursuit-diving predators, forage not only during the bottom phase but extensively while surfacing. More broadly, the integration of broken-stick segmentation with wiggle detection provides a simple, transferable framework for quantifying prey-capture attempts across pursuit-diving predators. This approach enhances inference from TDR data and contributes to a comparative understanding of how diving predators partition foraging effort within dives.

Temporal insights into afforestation: A 25-year study of woodland expansion - Julija Fediajevaite; Aaron Philips; John Tucker; Peter Buckley; Clive Steward; Sam Pettman; John Crawford; Petra Guy; Mark Tibbett; Nadia Barsoum; Brian J. Pickles (Forest Ecology and Management, 2026)

New Zealand blackcurrant extract has no effect on physiological and cardiovascular responses during low-intensity sustained intermittent isometric contractions in men - Stefano Montanari; Ben J. Lee; Sam D. Blacker; Matthew D. Cook; Mark E. T. Willems (European Journal of Applied Physiology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Antimicrobial resistance, genomic, and public health insights into Enterococcus spp. from Australian cattle - Rebecca Abraham; Shafi Sahibzada; Terence Lee; David Jordan; Kate McMillan; Glen Mellor; Lesley Duffy; Kittitat Lugsomya; Mark O'Dea; Sam Abraham; Robert Barlow (Veterinary Microbiology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Leveraging human mobility data to assess recreational activity across the United States’ most visited National Forest - Maksim Sergeyev; Mark A. Ditmer; Kira Z. Deming; Natasha Goedert; Michael K. Schwartz; Sam Massman; George Wittemyer (Journal of Outdoor Recreation and Tourism, 2025)

Response of Global Forest Management to Changes in Wood Demand - Bartlomiej Arendarczyk; Sam Rabin; Daniel Bampoh; Almut Arneth; Mark Rounsevell; Peter Alexander (Global Change Biology, 2025)
Global wood harvests have steadily increased over the last several decades and are projected to continue growing to match demand for wood products. How forest managers respond to changes in wood demand depends not just on timber prices and production costs but also on competition with other land uses, changes in forest productivity, and land use policies. Wood demand projections are sensitive to assumptions about socioeconomic development, including population growth, economic growth, and policy changes. Using a spatially detailed, process‐based land use model (LandSyMM), we simulate global wood demand, harvests, and forest management intensity under a range of future socioeconomic (Shared Socioeconomic Pathways; SSPs) and climate (Representative Concentration Pathways; RCPs) scenarios. Wood demand is projected for each country using a price‐elastic demand system that models changes in demand for industrial roundwood and wood fuel in response to changes in countries' incomes and endogenously modelled wood prices. Competition for land between forestry and agriculture, including for food and animal feed, is explicitly represented. We find that future wood harvests and forest management intensity vary considerably between scenarios. Different regions show heterogeneous responses to changes in wood demand, with global demand increasing between 27% (SSP1‐RCP2.6) and 102% (SSP3‐RCP7.0) by 2100. The results suggest that additional wood harvests will primarily be met through intensification of forest management and an increase in potential yields arising from climate change and CO 2 fertilisation. However, interactions between extreme events, nutrient limitations, and CO 2 ‐driven productivity gains remain uncertain and are not fully captured in the modelled results. Understanding how global forest management will change and its impact on forest structure, species composition, and carbon storage is critical in addressing climate change mitigation and biodiversity protection.

Utilising on-farm risk assessment data for the management of Johne’s disease in dairy cattle in Northern Ireland - Emma Nicole Taylor-Holt; Sam Strain; Nicholas Mark Taylor; Sitira Williams; Nicholas Wheelhouse; James Hanks; Peter Guy Orpin; David C. Rose; Abel Bulamu Ekiri (Preventive Veterinary Medicine, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Conservation changed but not divided - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Amy Hinsley; Sadiq Jaffer; et al. (Trends in Ecology & Evolution, 2025)

Current trends and biases in groundwater modelling using the community-driven groundwater model portal (GroMoPo) - Daniel Zamrsky; Sacha Ruzzante; Kyle Compare; Daniel Kretschmer; Sam Zipper; Kevin M. Befus; Robert Reinecke; Yara Pasner; Tom Gleeson; Kristen Jordan; Mark Cuthbert; Anthony M. Castronova; et al. (Hydrogeology Journal, 2025)
Groundwater, Earth’s largest nonfrozen freshwater reservoir, is vital for water supply security. Groundwater models help to manage complex domestic, agricultural, and industrial water demands while preserving ecosystem health under climate change. The community-driven groundwater model portal (GroMoPo) hosts groundwater model metadata to analyse biases and distribution of groundwater models. Over 450 models are currently featured on GroMoPo, with most models from high-GDP countries at local-to-regional scales. The GroMoPo initiative addresses current knowledge gaps and facilitates future collaboration and data sharing.

Counteracting uncertainty: exploring the impact of anxiety on updating predictions about environmental states - David Harris; Tom Arthur; Mark Wilson; Ben Le Gallais; Thomas Parsons; Ally Dill; Sam Vine (Biological Cybernetics, 2025)
Anxious emotional states disrupt decision-making and control of dexterous motor actions. Computational work has shown that anxiety-induced uncertainty alters the rate at which we learn about the environment, but the subsequent impact on the predictive beliefs that drive action control remains to be understood. In the present work we tested whether anxiety alters predictive (oculo)motor control mechanisms. Thirty participants completed an experimental task that consisted of manual interception of a projectile performed in virtual reality. Participants were subjected to conditions designed to induce states of high or low anxiety using performance incentives and social-evaluative pressure. We measured subsequent effects on physiological arousal, self-reported state anxiety, and eye movements. Under high pressure conditions we observed visual sampling of the task environment characterised by higher variability and entropy of position prior to release of the projectile, consistent with an active attempt to reduce uncertainty. Computational modelling of predictive beliefs, using gaze data as inputs to a partially observable Markov decision process model, indicated that trial-to-trial updating of predictive beliefs was reduced during anxiety, suggesting that updates to priors were constrained. Additionally, state anxiety was related to a less deterministic mapping of beliefs to actions. These results support the idea that organisms may attempt to counter anxiety-related uncertainty by moving towards more familiar and certain sensorimotor patterns.

The potential for AI to revolutionize conservation: a horizon scan - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Francis Gassert; Amy Hinsley; et al. (Trends in Ecology & Evolution, 2025)

“I’m like, whatever you want me to be. I’m the flavor of the day”: A mixed-methods study of the food dispositions and behaviors of mixed-race individuals - Mark Cleveland; Chenzi Feng Zhao; Sam Ghebrai (Food Quality and Preference, 2024)

Health impact of policies to reduce agriculture-related air pollutants in the UK: The relative contribution of change in PM2.5 exposure and diets to morbidity and mortality - Silvia Pastorino; Ai Milojevic; Rosemary Green; Rachel Beck; Edward Carnell; Patricia Eustachio Colombo; Tom Misselbrook; Mark Miller; Stefan Reis; Sam Tomlinson; Massimo Vieno; James Milner (Environmental Research, 2024)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

Knowledge co-production for identifying indicators and prioritising solutions for food and land system sustainability in Australia - Romy L. Zyngier; Carla L. Archibald; Brett A. Bryan; Haley Lambert; Enayat A. Moallemi; Mark Elliott; Mark Lawrence; Jane Hutchinson; Lauren T. Bennett; Timothy Reeves; Matthew Pryor; Ulrika Lindholm; et al. (Sustainability Science, 2024)
Achieving sustainable Australian food and land systems requires the rapid implementation and scaling up of a broad suite of solutions to meet the Sustainable Development Goals (SDGs). Decision-making frameworks are needed to identify suitable indicators and prioritise solutions at national scales to inform sustainability transitions. Using a knowledge co-production framework, we convened 150 stakeholders from 100 + organisations to identify 18 nationally relevant indicators that aligned with critical SDGs describing a sustainable food and land system for Australia, in addition to 78 key solutions (supply- and demand-side) to enable progress against these indicators. We then asked subject matter experts to code the impact of each solution on each indicator using an adapted interaction mapping method accounting for uncertainty. The solution category ‘Protecting and restoring nature’, which included solutions targeting conservation and restoration, showed the highest potential for capturing synergies and avoiding trade-offs across multiple indicators. This category exhibited 34.6% of total major synergies, supporting the achievement of clean water and sanitation (SDG6), economic growth (SDG12), life under water (SDG14), and life on land (SDG15). The solution category ‘Carbon sequestration’, which included technological and biological carbon dioxide removal solutions, had the highest number of trade-offs with individual sustainability indicators (42.3%), particularly those relating to zero hunger (SDG2), wellbeing (SDG3), SDG6, SDG14, and SDG15. Our framework can be used to inform future research investment, support the prioritisation of solutions for quantitative modelling, and inform discussions with stakeholders and policymakers for transforming national-scale food and land systems in alignment with the SDGs.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Traversing the land‐sea interface: A climate change risk assessment of terrestrially breeding marine predators - Milan Sojitra; Stuart Corney; Mark Hemer; Sheryl Hamilton; Julie McInnes; Sam Thalmann; Mary‐Anne Lea (Global Change Biology, 2024)
Terrestrially breeding marine predators have experienced shifts in species distribution, prey availability, breeding phenology, and population dynamics due to climate change worldwide. These central‐place foragers are restricted within proximity of their breeding colonies during the breeding season, making them highly susceptible to any changes in both marine and terrestrial environments. While ecologists have developed risk assessments to evaluate climate risk in various contexts, these often overlook critical breeding biology data. To address this knowledge gap, we developed a trait‐based risk assessment framework, focusing on the breeding season and applying it to marine predators breeding in parts of Australian territory and Antarctica. Our objectives were to quantify climate change risk, identify specific threats, and establish an adaptable assessment framework. The assessment considered 25 criteria related to three risk components: vulnerability, exposure, and hazard, while accounting for uncertainty. We employed a scoring system that integrated a systematic literature review and expert elicitation for the hazard criteria. Monte Carlo sensitivity analysis was conducted to identify key factors contributing to overall risk. We identified shy albatross ( Thalassarche cauta ), southern rockhopper penguins ( Eudyptes chrysocome ), Australian fur seals ( Arctocephalus pusillus doriferus ), and Australian sea lions ( Neophoca cinerea ) with high climate urgency. Species breeding in lower latitudes, as well as certain eared seal, albatross, and penguin species, were particularly at risk. Hazard and exposure explained the most variation in relative risk, outweighing vulnerability. Key climate hazards affecting most species include extreme weather events, changes in habitat suitability, and prey availability. We emphasise the need for further research, focusing on at‐risk species, and filling knowledge gaps (less‐studied hazards, and/or species) to provide a more accurate and robust climate change risk assessment. Our findings offer valuable insights for conservation efforts, given that monitoring and implementing climate adaptation strategies for land‐dependent marine predators is more feasible during their breeding season.

Experiences with wildfire are associated with private landowners’ management decisions, relationships, and perceptions of risk - Clare Aslan; Ryan Tarver; Mark Brunson; Sam Veloz; Ben Sikes; Rebecca Epanchin-Niell (Landscape and Urban Planning, 2024)

The influence of multidecadal climate variability and abrupt landscape change on terrestrial ecosystem composition and fire regime in the upper Columbia River basin - A high-resolution Holocene perspective - Sam Mark; Cathy Whitlock; Mark Abbott; Byron Steinman; Alejandro Fernandez; Jennifer Steeple (Quaternary Science Reviews, 2024)

Criteria and workflow for selecting saline formations for carbon storage - Catherine Callas; J. Steve Davis; Sarah D. Saltzer; Sam S. Hashemi; Gege Wen; Peter O. Gold; Mark D. Zoback; Sally M. Benson; Anthony R. Kovscek (International Journal of Greenhouse Gas Control, 2024)

Conservation prioritisation of genomic diversity to inform management of a declining mammal species - Brenton von Takach; Skye F. Cameron; Teigan Cremona; Mark D.B. Eldridge; Diana O. Fisher; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; Ben L. Phillips; Ian J. Radford; Kate Rick; Peter B.S. Spencer; et al. (Biological Conservation, 2024)

Mapping the shared socio-economic pathways onto the Nature Futures Framework at the global scale - Peter Alexander; Roslyn Henry; Sam Rabin; Almut Arneth; Mark Rounsevell (Sustainability Science, 2023)
The Nature Futures Framework (NFF) was developed for the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES) to explore scenarios that represent a diversity of positive relationships between humans and nature. Widely used in global environmental assessments, the shared socio-economic pathways (SSPs) in combination with the representative concentration pathways (RCPs) were developed for climate change assessments. However, the relationship at a global level between the SSP–RCP scenario outcomes and the framing of the NFF around three value perspectives—Nature for Nature, Nature for Society, and Nature as Culture—has not been established. Here, we demonstrate a method to map onto the NFF value perspectives results from alternative SSP scenarios, each paired with an RCP consistent with the SSP storyline. For each of the NFF value perspectives, multiple elements were identified, each represented by one or more nature-focused indicators. Values for these indicators, for the different SSP scenario outcomes, were derived from an existing application of a global land system model, LandSyMM. A score for each indicator is estimated by comparing the indicator values against a normative target range. We find that only SSP1 provides greater benefits for Nature as Culture and Nature for Society relative to a 2010 baseline. Overall, the SSP scenarios provide fewer benefits for Nature for Nature, consistent with a bias towards the provision of material over non-material ecosystem services. The results demonstrate that the SSP–RCP scenario framing captures some, but not all, of the dimensions of nature and that alternative scenario framings, such as the NFF, are needed to study a broader range of biodiversity and ecosystem related questions as well as exploring positive futures.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Proximity to human settlement is directly related to carriage of critically important antimicrobial-resistant Escherichia coli and Klebsiella pneumoniae in Silver Gulls - Shewli Mukerji; Shafi Sahibzada; Rebecca Abraham; Marc Stegger; David Jordan; David J. Hampson; Mark O’Dea; Terence Lee; Sam Abraham (Veterinary Microbiology, 2023)

Plasma metallomics reveals potential biomarkers and insights into the ambivalent associations of elements with acute myocardial infarction - Si Ying Lim; Hiranya Dayal; Song Jie Seah; Regina Pei Woon Tan; Zhi En Low; Anna Karen Carrasco Laserna; Sock Hwee Tan; Mark Y. Chan; Sam Fong Yau Li (Journal of Trace Elements in Medicine and Biology, 2023)

Exploring the potential of MIL-derived nanocomposites to enhance performance of lithium-ion batteries - Bhavana Joshi; Edmund Samuel; Yong-Il Kim; Hae-Seok Lee; Mark T. Swihart; Sam S. Yoon (Chemical Engineering Journal, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Seasonal drivers of productivity and calcification in the coral Platygyra carnosa in a subtropical reef - Walter Dellisanti; Jeffery T. H. Chung; Sam K. F. Yiu; Ryan Ho Leung Tsang; Put Ang; Yip Hung Yeung; Jian-Wen Qiu; Shelby E. McIlroy; Mark L. Wells; Jiajun Wu; Leo Lei Chan (Frontiers in Marine Science, 2023)
Scleractinian corals are increasingly subjected to local stressors combined with global changes. In subtropical areas, corals exhibit metabolic plasticity and resilience in response to variability and extremes in local temperature, salinity, and light; however, the physiological mechanisms by which corals acclimate or adapt to these changing conditions remain disputed. We assessed the physiological status of the coral Platygyra carnosa during a two-year in situ monitoring survey. To obtain metabolic rates (respiration and photosynthesis), photochemical efficiency (Fv / Fm), and biocalcification measurements, non-invasive techniques such as underwater respirometry, Pulse Amplitude Modulated (PAM) fluorometry, total alkalinity measurements, and digital photography were used. Our findings show clear seasonality in water quality parameters, which affected coral health. Elevated temperatures during the summer were below the maximum monthly mean < 31°C) but reduced the energetic productivity of corals (-44% relative to winter). Fluctuations in salinity (25–38 ppt) and pH (7.65–8.44) were linked to rainfall and reduced calcification rates. The conditions during the spring were favorable for coral metabolism and calcification (+20% relative to summer). Overall, our research demonstrates that the metabolic plasticity of P. carnosa in response to shifts in seawater quality allows this species to survive ongoing environmental change. Our in situ observations provide fundamental insights into coral response mechanisms under changing environmental conditions and contribute to projections of coral health under future scenarios of global change.

Unifying biological field observations to detect and compare ocean acidification impacts across marine species and ecosystems: what to monitor and why - Steve Widdicombe; Kirsten Isensee; Yuri Artioli; Juan Diego Gaitán-Espitia; Claudine Hauri; Janet A. Newton; Mark Wells; Sam Dupont (Ocean Science, 2023)
Approximately one-quarter of the CO2 emitted to the atmosphere annually from human activities is absorbed by the ocean, resulting in a reduction of seawater pH and shifts in seawater carbonate chemistry. This multi-decadal process, termed “anthropogenic ocean acidification” (OA), has been shown to have detrimental impacts on marine ecosystems. Recent years have seen a globally coordinated effort to measure the changes in seawater chemistry caused by OA, with best practices now available for these measurements. In contrast to these substantial advances in observing physicochemical changes due to OA, quantifying their biological consequences remains challenging, especially from in situ observations under real-world conditions. Results from 2 decades of controlled laboratory experiments on OA have given insight into the likely processes and mechanisms by which elevated CO2 levels affect biological process, but the manifestation of these process across a plethora of natural situations has yet to be fully explored. This challenge requires us to identify a set of fundamental biological and ecological indicators that are (i) relevant across all marine ecosystems, (ii) have a strongly demonstrated link to OA, and (iii) have implications for ocean health and the provision of ecosystem services with impacts on local marine management strategies and economies. This paper draws on the understanding of biological impacts provided by the wealth of previous experiments, as well as the findings of recent meta-analyses, to propose five broad classes of biological indicators that, when coupled with environmental observations including carbonate chemistry, would allow the rate and severity of biological change in response to OA to be observed and compared. These broad indicators are applicable to different ecological systems, and the methods for data analysis suggested here would allow researchers to combine biological response data across regional and global scales by correlating rates of biological change with the rate of change in carbonate chemistry parameters. Moreover, a method using laboratory observation to design an optimal observing strategy (frequency and duration) and observe meaningful biological rates of change highlights the factors that need to be considered when applying our proposed observation strategy. This innovative observing methodology allows inclusion of a wide diversity of marine ecosystems in regional and global assessments and has the potential to increase the contribution of OA observations from countries with developing OA science capacity.

Population genomics of a predatory mammal reveals patterns of decline and impacts of exposure to toxic toads - Brenton von Takach; Louis Ranjard; Christopher P. Burridge; Skye F. Cameron; Teigan Cremona; Mark D. B. Eldridge; Diana O. Fisher; Stephen Frankenberg; Brydie M. Hill; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; et al. (Molecular Ecology, 2022)
Mammal declines across northern Australia are one of the major biodiversity loss events occurring globally. There has been no regional assessment of the implications of these species declines for genomic diversity. To address this, we conducted a species‐wide assessment of genomic diversity in the northern quoll ( Dasyurus hallucatus ), an Endangered marsupial carnivore. We used next generation sequencing methods to genotype 10,191 single nucleotide polymorphisms (SNPs) in 352 individuals from across a 3220‐km length of the continent, investigating patterns of population genomic structure and diversity, and identifying loci showing signals of putative selection. We found strong heterogeneity in the distribution of genomic diversity across the continent, characterized by (i) biogeographical barriers driving hierarchical population structure through long‐term isolation, and (ii) severe reductions in diversity resulting from population declines, exacerbated by the spread of introduced toxic cane toads ( Rhinella marina ). These results warn of a large ongoing loss of genomic diversity and associated adaptive capacity as mammals decline across northern Australia. Encouragingly, populations of the northern quoll established on toad‐free islands by translocations appear to have maintained most of the initial genomic diversity after 16 years. By mapping patterns of genomic diversity within and among populations, and investigating these patterns in the context of population declines, we can provide conservation managers with data critical to informed decision‐making. This includes the identification of populations that are candidates for genetic management, the importance of remnant island and insurance/translocated populations for the conservation of genetic diversity, and the characterization of putative evolutionarily significant units.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Swelling of Compacted Clay as Affected by Quantity of Water Intake and Soil Structure - Shay Nachum; Mark Talesnick; Sam Frydman (Geotechnical and Geological Engineering, 2022)

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Storm-driven across-shelf oceanic flows into coastal waters - Sam Jones; Mark Inall; Marie Porter; Jennifer A. Graham; Finlo Cottier (Ocean Science, 2020)
The North Atlantic Ocean and northwest European shelf experience intense low-pressure systems during the winter months. The effect of strong winds on shelf circulation and water properties is poorly understood as observations during these episodes are rare, and key flow pathways have been poorly resolved by models up to now. We compare the behaviour of a cross-shelf current in a quiescent period in late summer, with the same current sampled during a stormy period in midwinter, using drogued drifters. Concurrently, high-resolution time series of current speed and salinity from a coastal mooring are analysed. A Lagrangian analysis of modelled particle tracks is used to supplement the observations. Current speeds at 70 m during the summer transit are 10–20 cm s−1, whereas on-shelf flow reaches 60 cm s−1 during the winter storm. The onset of high across-shelf flow is identified in the coastal mooring time series, both as an increase in coastal current speed and as an abrupt increase in salinity from 34.50 to 34.85, which lags the current by 8 d. We interpret this as the wind-driven advection of outer-shelf (near-oceanic) water towards the coastline, which represents a significant change from the coastal water pathways which typically feed the inner shelf. The modelled particle analysis supports this interpretation: particles which terminate in coastal waters are recruited locally during the late summer, but recruitment switches to the outer shelf during the winter storm. We estimate that during intense storm periods, on-shelf transport may be up to 0.48 Sv, but this is near the upper limit of transport based on the multi-year time series of coastal current and salinity. The likelihood of storms capable of producing these effects is much higher during positive North Atlantic Oscillation (NAO) winters.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Exploring how material cues drive sensorimotor prediction across different levels of autistic-like traits - Tom Arthur; Sam Vine; Mark Brosnan; Gavin Buckingham (Experimental Brain Research, 2019)

Mahseer (Tor spp.) fishes of the world: status, challenges and opportunities for conservation - Adrian C. Pinder; J. Robert Britton; Andrew J. Harrison; Prakash Nautiyal; Shannon D. Bower; Steven J. Cooke; Steve Lockett; Mark Everard; Unmesh Katwate; K. Ranjeet; Sam Walton; Andy J. Danylchuk; et al. (Reviews in Fish Biology and Fisheries, 2019)

Adaptation of global land use and management intensity to changes in climate and atmospheric carbon dioxide - Peter Alexander; Sam Rabin; Peter Anthoni; Roslyn Henry; Thomas A. M. Pugh; Mark D. A. Rounsevell; Almut Arneth (Global Change Biology, 2018)
Land use contributes to environmental change, but is also influenced by such changes. Climate and atmospheric carbon dioxide ( CO 2 ) levels’ changes alter agricultural crop productivity, plant water requirements and irrigation water availability. The global food system needs to respond and adapt to these changes, for example, by altering agricultural practices, including the crop types or intensity of management, or shifting cultivated areas within and between countries. As impacts and associated adaptation responses are spatially specific, understanding the land use adaptation to environmental changes requires crop productivity representations that capture spatial variations. The impact of variation in management practices, including fertiliser and irrigation rates, also needs to be considered. To date, models of global land use have selected agricultural expansion or intensification levels using relatively aggregate spatial representations, typically at a regional level, that are not able to characterise the details of these spatially differentiated responses. Here, we show results from a novel global modelling approach using more detailed biophysically derived yield responses to inputs with greater spatial specificity than previously possible. The approach couples a dynamic global vegetative model ( LPJ ‐ GUESS ) with a new land use and food system model ( PLUM v2), with results benchmarked against historical land use change from 1970. Land use outcomes to 2100 were explored, suggesting that increased intensity of climate forcing reduces the inputs required for food production, due to the fertilisation and enhanced water use efficiency effects of elevated atmospheric CO 2 concentrations, but requiring substantial shifts in the global and local patterns of production. The results suggest that adaptation in the global agriculture and food system has substantial capacity to diminish the negative impacts and gain greater benefits from positive outcomes of climate change. Consequently, agricultural expansion and intensification may be lower than found in previous studies where spatial details and processes consideration were more constrained.

New Zealand blackcurrant extract enhances fat oxidation during prolonged cycling in endurance-trained females - Juliette A. Strauss; Mark E. T. Willems; Sam O. Shepherd (European Journal of Applied Physiology, 2018)

Autologous Cell Seeding in Tracheal Tissue Engineering - Elizabeth F. Maughan; Robert E. Hynds; Toby J. Proctor; Sam M. Janes; Martin Elliott; Martin A. Birchall; Mark W. Lowdell; Paolo De Coppi (Current Stem Cell Reports, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Discordant CSF/plasma HIV-1 RNA in patients with unexplained low-level viraemia - Sam Nightingale; Anna Maria Geretti; Apostolos Beloukas; Martin Fisher; Alan Winston; Laura Else; Mark Nelson; Stephen Taylor; Andrew Ustianowski; Jonathan Ainsworth; Richard Gilson; Lewis Haddow; et al. (Journal of NeuroVirology, 2016)

Regional engagement and spatial modelling for natural resource management planning - Wayne S. Meyer; Brett A. Bryan; David M. Summers; Greg Lyle; Sam Wells; Josie McLean; Mark Siebentritt (Sustainability Science, 2016)

New Zealand blackcurrant extract improves cycling performance and fat oxidation in cyclists - Matthew David Cook; Stephen David Myers; Sam David Blacker; Mark Elisabeth Theodorus Willems (European Journal of Applied Physiology, 2015)

Foraging distribution of a tropical seabird supports Ashmole’s hypothesis of population regulation - Steffen Oppel; Annalea Beard; Derren Fox; Elizabeth Mackley; Eliza Leat; Leeann Henry; Elizabeth Clingham; Nathan Fowler; Jolene Sim; Julia Sommerfeld; Nicola Weber; Sam Weber; et al. (Behavioral Ecology and Sociobiology, 2015)

Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Brian Booth; Mark E. Arnold; Binodh DeSilva; Lakshmi Amaravadi; Sherri Dudal; Eric Fluhler; Boris Gorovits; Sam H. Haidar; John Kadavil; Steve Lowes; Robert Nicholson; Marie Rock; et al. (The AAPS Journal, 2015)

Over 75 years of zooplankton data from Australia - Claire H. Davies; Amelia J. Armstrong; Mark Baird; Frank Coman; Steven Edgar; Daniel Gaughan; Jack Greenwood; Felipe Gusmão; Natasha Henschke; J. Anthony Koslow; Sophie C. Leterme; A. David McKinnon; et al. (Ecology, 2014)
Zooplankton are the key trophic link between primary producers and fish in pelagic ecosystems. Historically, there are few zooplankton time series in Australia, with no data sets longer than two years prior to 2008. Here we compile 98 676 abundance records of more than 1000 zooplankton taxa from unpublished research cruises, student projects, published literature, and the recent Integrated Marine Observing System (IMOS). This data set covers the entire coastal and shelf region of Australia and dates back to 1938. Most records are for copepods, but there are also data for other taxa such as decapods, chaetognaths, thaliaceans, appendicularians, and cladocerans. Metadata are provided for each record, including dates, coordinates, and information on mesh size and sampling methods. To facilitate analysis across the multiple data sets, we have updated the species names according to the World Register of Marine Species (WoRMS) and converted units to abundance per cubic meter. These data will be valuable for studies of biodiversity, biogeography, impacts of climate change, and ecosystem health. We encourage researchers holding additional Australian zooplankton data to contact us and contribute their data to the data set so we can periodically publish updates.

Assessing Multiregion Avian Benefits from Strategically Targeted Agricultural Buffers - KRISTINE O. EVANS; L. WES BURGER; SAM RIFFELL; MARK D. SMITH (Conservation Biology, 2014)
Mounting evidence of wildlife population gains from targeted conservation practices has prompted the need to develop and evaluate practices that are integrated into production agriculture systems and targeted toward specific habitat objectives. However, effectiveness of targeted conservation actions across broader landscapes is poorly understood. We evaluated multiregion, multispecies avian densities on row‐crop fields with native grass field margins (i.e., buffers) as part of the first U.S. agricultural conservation practice designed to support habitat and population recovery objectives of a national wildlife conservation initiative. We coordinated breeding season point transect surveys for 6 grassland bird species on 1151 row‐crop fields with and without native grass buffers (9–37 m) in 14 U.S. states (10 ecoregions) from 2006 to 2011. In most regions, breeding season densities of 5 of 6 targeted bird species were greater in the 500‐m surrounding survey points centered on fields with native grass buffers than in landscapes without buffers. Relative effect sizes were greatest for Northern Bobwhite ( Colinus virginianus ), Dickcissel ( Spiza americana ), and Field Sparrow ( Spizella pusilla ) in the Mississippi Alluvial Valley and Eastern Tallgrass Prairie regions. Other species (e.g., Eastern Meadowlark [ Sturnella magna ], Grasshopper Sparrow [ Ammodramus savannarum ]) exhibited inconsistent relative effect sizes. Bird densities on fields with and without buffers were greatest in the Central Mixed‐grass Prairie region. Our results suggest that strategic use of conservation buffers in regions with the greatest potential for relative density increases in target species will elicit greater range‐wide population response than diffuse, uninformed, and broadly distributed implementation of buffers. We recommend integrating multiple conservation practices in broader agricultural landscapes to maximize conservation effectiveness for a larger suite of species. Evaluación de los Beneficios de la Mutliregionalidad de Aves a Partir de Amortiguadores Agriculturales Estratégicamente Señalados

Nitric oxide in the breath of bottlenose dolphins: Effects of breath hold duration, feeding, and lung disease - Laura C. Yeates; Kevin P. Carlin; Mark Baird; Stephanie Venn‐Watson; Sam Ridgway (Marine Mammal Science, 2014)
Breath analysis, including measurement of nitric oxide ( NO ), is a noninvasive diagnostic tool that may help evaluate cetacean health. This is the first report on the effects of breath hold duration, feeding, and lung disease on NO in dolphin exhaled breath. Three healthy dolphins were trained to hold their breath for 30, 60, 90, and 120 s and then exhale into an underwater funnel. Exhaled NO values from 157 breath samples were compared among three healthy dolphins by breath hold time and after fasting and feeding. Exhaled NO values were also measured in two dolphins with pulmonary disease. NO in dolphin breath was higher compared to ambient air; healthy dolphins had higher NO concentrations in their breath after feeding compared to after overnight fasting; and there were no significant differences in exhaled NO levels by breath hold duration. A dolphin with Mycoplasma ‐associated pneumonia and chronic gastrointestinal disease had higher postprandial exhaled NO levels compared to healthy controls. This study demonstrates, contrary to previous publications, that dolphins exhale NO . Given the high standard deviations present in exhaled breath NO values, future studies are needed to further standardize collection methods or identify more reliable samples ( e.g ., blood).

The association of ultraviolet radiation-B (305 nm), season of diagnosis, and latitude on the survival outcome of prostate cancer in the high UV environment of Australia - Visalini Nair-Shalliker; David P. Smith; Sam Egger; Mark S. Clements; Md. Bayzidur Rahman; Bruce K. Armstrong (Cancer Causes & Control, 2013)

Evaluation of terrestrial carbon cycle models for their response to climate variability and to CO 2 trends - Shilong Piao; Stephen Sitch; Philippe Ciais; Pierre Friedlingstein; Philippe Peylin; Xuhui Wang; Anders Ahlström; Alessandro Anav; Josep G. Canadell; Nan Cong; Chris Huntingford; Martin Jung; et al. (Global Change Biology, 2013)
The purpose of this study was to evaluate 10 process‐based terrestrial biosphere models that were used for the IPCC fifth Assessment Report. The simulated gross primary productivity ( GPP ) is compared with flux‐tower‐based estimates by Jung et al . [ Journal of Geophysical Research 116 (2011) G00J07] ( JU 11). The net primary productivity ( NPP ) apparent sensitivity to climate variability and atmospheric CO 2 trends is diagnosed from each model output, using statistical functions. The temperature sensitivity is compared against ecosystem field warming experiments results. The CO 2 sensitivity of NPP is compared to the results from four Free‐Air CO 2 Enrichment ( FACE ) experiments. The simulated global net biome productivity ( NBP ) is compared with the residual land sink ( RLS ) of the global carbon budget from Friedlingstein et al . [ Nature Geoscience 3 (2010) 811] ( FR 10). We found that models produce a higher GPP (133 ± 15 Pg C yr −1 ) than JU 11 (118 ± 6 Pg C yr −1 ). In response to rising atmospheric CO 2 concentration, modeled NPP increases on average by 16% (5–20%) per 100 ppm, a slightly larger apparent sensitivity of NPP to CO 2 than that measured at the FACE experiment locations (13% per 100 ppm). Global NBP differs markedly among individual models, although the mean value of 2.0 ± 0.8 Pg C yr −1 is remarkably close to the mean value of RLS (2.1 ± 1.2 Pg C yr −1 ). The interannual variability in modeled NBP is significantly correlated with that of RLS for the period 1980–2009. Both model‐to‐model and interannual variation in model GPP is larger than that in model NBP due to the strong coupling causing a positive correlation between ecosystem respiration and GPP in the model. The average linear regression slope of global NBP vs. temperature across the 10 models is −3.0 ± 1.5 Pg C yr −1 °C −1 , within the uncertainty of what derived from RLS (−3.9 ± 1.1 Pg C yr −1 °C −1 ). However, 9 of 10 models overestimate the regression slope of NBP vs. precipitation, compared with the slope of the observed RLS vs. precipitation. With most models lacking processes that control GPP and NBP in addition to CO 2 and climate, the agreement between modeled and observation‐based GPP and NBP can be fortuitous. Carbon–nitrogen interactions (only separable in one model) significantly influence the simulated response of carbon cycle to temperature and atmospheric CO 2 concentration, suggesting that nutrients limitations should be included in the next generation of terrestrial biosphere models.

The ice age ecologist: testing methods for reserve prioritization during the last global warming - John W. Williams; Heather M. Kharouba; Sam Veloz; Mark Vellend; Jason McLachlan; Zhengyu Liu; Bette Otto‐Bliesner; Feng He (Global Ecology and Biogeography, 2013)
Aim We play the role of an ice age ecologist (IAE) charged with conserving biodiversity during the climate changes accompanying the last deglaciation. We develop reserve‐selection strategies for the IAE and check them against rankings based on modern data. Location Northern and eastern North America. Methods Three reserve‐selection strategies are developed. (1) Abiotic: the IAE uses no information about species–climate relationships, instead maximizing the climatic and geographic dispersion of reserves. (2) Species distribution models (SDMs): the IAE uses boosted‐regression trees calibrated against pollen data and CCSM3 palaeoclimatic simulations from 21 to 15 ka bp to predict modern taxon distributions, then uses these as input to the Z onation reserve‐ranking program. (3) Rank‐and‐regress: regression models are used to identify climatic predictors of zonation rankings. All strategies are assessed against a Z onation ranking based on modern pollen distributions. Analysis units are ecoregions and grid cells. Results The abiotic strategy has a negative or no correlation between predicted and actual rankings. The SDM‐based strategy fares better, with a significantly positive area‐corrected correlation ( r = 0.474, P 0.001) between predicted and actual rankings. Predictive ability drops when grid cells are the analysis unit ( r = 0.217, P = 0.058). Predictive ability for the rank‐and‐regress strategy is similar to the SDM results. Main conclusions For the IAE, SDMs improve the predictive ability of reserve‐selection strategies. However, predictive ability is limited overall, probably due to shifted realized niches during past no‐analogue climates, new species interactions as species responded individually to climate change, and other environmental changes not included in the model. Twenty‐first‐century conservation planning also faces these challenges, and is further complicated by other anthropogenic impacts. The IAE's limited success does not preclude the use of climate scenarios and niche‐based SDMs when developing adaptation strategies, but suggests that such tools offer at best only a rough guide to identifying possible areas of future conservation value.

Estimating prevalence of distant metastatic breast cancer: a means of filling a data gap - Mark S. Clements; David M. Roder; Xue Qin Yu; Sam Egger; Dianne L. O’Connell (Cancer Causes & Control, 2012)

The effect of a carbohydrate beverage on the physiological responses during prolonged load carriage - Sam D. Blacker; Neil C. Williams; Joanne L. Fallowfield; Mark E. T. Willems (European Journal of Applied Physiology, 2011)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Efficacy of Vegetated Buffers in Preventing Transport of Fecal Coliform Bacteria from Pasturelands - Timothy J. Sullivan; James A. Moore; David R. Thomas; Eric Mallery; Kai U. Snyder; Mark Wustenberg; Judith Wustenberg; Sam D. Mackey; Deian L. Moore (Environmental Management, 2007)

The effects of climate variability on zooplankton and basking shark ( Cetorhinus maximus ) relative abundance off southwest Britain - PETER A. COTTON; DAVID W. SIMS; SAM FANSHAWE; MARK CHADWICK (Fisheries Oceanography, 2005)
At small spatial scales basking sharks ( Cetorhinus maximus ) forage selectively on zooplankton along thermal fronts, but the factors influencing broader scale patterns in their abundance and distribution remain largely unknown. Using long‐term sightings data collected off southwest Britain between 1988 and 2001, we show that the number of basking sharks recorded was highly correlated with abiotic factors, principally sea surface temperature (SST) and the lagged effect of SST in the previous month, but only very weakly to zooplankton density. This suggests that the changes in number of basking sharks recorded over large spatio‐temporal scales are more closely related to the availability of climate‐driven thermal resources than prey availability, whereas the converse is supported by previous studies at local scales. Taken together, these results imply scale‐dependent behavioural responses in basking sharks, with small‐scale foraging movements linked by broad scale responses to temperature variation.

Privatizing canal irrigation - Mark Svendsen; Fernando Gonzalez; Sam Johnson (Irrigation and Drainage, 2003)
Widespread dissatisfaction with state management of canal irrigation systems has focused intense interest on potential private sector remedies for the problems afflicting the sector. Privatization promises a number of benefits—lower operating costs, increased productivity, innovation, mobilization of capital, higher service quality, and larger service areas. However, canal irrigation is a natural monopoly, where the large capital investments required preclude multiple private service providers in a given service area. Nevertheless, the paper argues that there are a number of ways to take advantage of positive features of the private sector, without wasteful duplication of infrastructure or leaving farmers at the mercy of greedy investors. Three primary options—renewable management contracts, franchises, and self‐provision of services by clients—are described and illustrated. Another way to examine possibilities for privatization is to look at the types of organizations that provide irrigation services. The defining aspects of an organization are governance, source of funds, economic motive, and type of staff. The paper defines a set of five types of service providers based on these characteristics. These types are departments, authorities, districts, associations, and public utilities. The characteristics of each are discussed, with examples. To rise above the basic performance floor provided by a public bureaucracy, an institutional structure including private elements requires a supporting policy environment. Critical elements of a supportive environment include policy stability, legal respect for contracts and agreements, and reasonably impartial regulation, allocation, and adjudication. In the absence of a sufficiently supportive national governance environment, private elements in the irrigation management system are unlikely to flourish or, conversely, may have the ability to take advantage of weaker parties. Copyright © 2003 John Wiley & Sons, Ltd.

Fast Neutron Irradiation for Prostate Cancer - Jeffrey D. Forman; Mark Yudelev; Susan Bolton; Sam Tekyi-Mensah; Richard Maughan (Cancer and Metastasis Reviews, 2002)